2003
DOI: 10.1152/ajpgi.00213.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ligands that increase cAMP on caerulein-induced zymogen activation in pancreatic acini

Abstract: The pathological activation of proteases within the pancreatic acinar cell is critical to initiating pancreatitis. Stimulation of acinar cells with supraphysiological concentrations of the CCK analog caerulein (CER) leads to protease activation and pancreatitis. Agents that sensitize the acinar cell to the effects of CCK might contribute to disease. The effects of physiological ligands that increase acinar cell cAMP [secretin, VIP, and pituitary adenylate cyclase activating peptide (PACAP)] on CER-induced resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 13 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…Intracellular signaling molecules such as the MAPKs, cAMP, protein kinase C, and NF-B are known to be activated upon induction of acute pancreatitis (Tando et al, 1999;Lu et al, 2003;Bi and Williams, 2004;Thrower et al, 2008). Previous studies showed that activation of ERK1/2 and JNK induced cytokine production, and inhibition of ERK1/2 and JNK showed protective effects (Samuel et al, 2006(Samuel et al, , 2008Namkung et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular signaling molecules such as the MAPKs, cAMP, protein kinase C, and NF-B are known to be activated upon induction of acute pancreatitis (Tando et al, 1999;Lu et al, 2003;Bi and Williams, 2004;Thrower et al, 2008). Previous studies showed that activation of ERK1/2 and JNK induced cytokine production, and inhibition of ERK1/2 and JNK showed protective effects (Samuel et al, 2006(Samuel et al, , 2008Namkung et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings raise the possible concerns of PACAP in the pathophysiology of pancreatitis (12,14). Recently, it has been reported that development of human chronic pancreatitis is associated with intrapancreatic accumulation of PACAP (15).…”
Section: Discussionmentioning
confidence: 99%
“…2 and Table 1). PACAP or CCK alone has little effect on amylase secretion from pancreatic acinar cells, while in combination they markedly increase the amylase secretion by sensitizing the acinar cells to CCK-induced zymogen activation (12). Epac/Rap1 signals play an essential role as a common signal for both CCK-and cAMP-evoked amylase secretions in pancreatic acinar cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic acinar cells, secretin as well as other agents that increase cAMP have little effect on zymogen activation alone but sensitize the response of agents that increase intracellular calcium such as cerulein or cholecystokinin (11,12). In pancreatic acini, it was reported that a cell-permeable cAMP inhibitor (Rp-8Br-cAMP) reduces the sensitization induced by vasoactive intestinal peptide and 8Br-cAMP to low and high doses of cerulein (11). It also reduces chymotrypsin activation induced by high doses of cerulein alone.…”
Section: Blockade Of Multidrug Resistance-associated Proteins Aggravamentioning
confidence: 99%